التدابير الوقائية الشرعية لجنوح الأحداث - باهي, ياسين; مجيدي, المانع (جامعة الوادي - University of Eloued, 2022)
ملخص: يأتي هذا البحث المعنون كالآتي: "التدابير الوقائية الشرعية لجنوح الأحداث" ليوضِّح أهمّ التدابير الشرعية الوقائية للحفاظ على الأحداث من الانحراف، مجيبا على إشكال رئيس هو: "هل تعدّ التدابير الوقائية الشرعية عاملا مهمًّا في الحفاظ على الأحداث من الجنوح؟". وقد أجاب عنه مبيّنا أنّ الإسلام جاء لتنظيم حياة النّاس تنظيمًا دقيقا مراعيًا الحقوق والواجبات في ذلك، ممَّا يكفل لهم السّعادة والخير في الدّارين، واختصَّ منهم شريحة الأحداث، فقد اهتم بها اهتمامًا بالغًا، كونها تمثّل حاضر الأمّة ومستقبلها، وممّا يستوجب التقدير لمنهج الإسلام القويم في الإسلام أنّه لم يضع وسيلة وقائية واحدة للحماية، وإنّما تعدّدت وسائله تعدّدًا قيّمًا؛ لأنّه منهج موضوع من أحكم الحاكمين الأعرف بأحوال الخلق. Abstract : This research, entitled: “Islamic precautionary measures to beware of juvenile delinquency” comes to clarify the most important preventive legal measures to keep juveniles from delinquency, answering a major problem: “Are Sharia preventive measures an important factor in preserving juvenile delinquency?” And he answered it, noting that Islam came to strictly organize people's lives, observing the rights and duties in it, which guarantees happiness and goodness in the two homes. And he specialized in among them the juvenile segment, as he took a keen interest in it because it represents the nation's present and future, What deserves appreciation for the correct method of Islam in Islam is that it did not put a single preventive means of protection, but its methods were valuable in number because it is a method that is established from Allah, who knows the condition of the creatures.
مقال
Keywords: التدابير ; الوقائية ; الشرعية ; جنوح ; الأحداث